2022
DOI: 10.1186/s12935-021-02412-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-133a targets YES1 to reduce cisplatin resistance in ovarian cancer by regulating cell autophagy

Abstract: Background Accumulating evidence has revealed that aberrant microRNA (miRNA) expression can affect the development of chemotherapy drug resistance by modulating the expression of relevant target proteins. Emerging evidence has demonstrated that miR-133a participates in the tumorigenesis of various cancers. However, whether miR-133a is associated with cisplatin resistance in ovarian cancer remains unclear. Objective To investigate the role of miR-13… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…The corresponding CP-resistant OC cell lines A2780CP and SKOV3/CDDP were constructed by our laboratory. Sensitive parental A2780S cells and SKOV3 cells were co-cultured with 10–80 μM CP (Sigma-Aldrich, St. Louis, MO) for 48 h, during which the concentration of CP was gradually increased [ 23 , 24 ]. After resuscitation, these cells were cultured in DMEM (Gibco, Carlsbad, CA) containing 10% FBS (Gibco), 100 U/mL penicillin and 100 μg/mL streptomycin in a 5% CO 2 incubator (BB15, Thermo Fisher Scientific Inc., Waltham, MA) at 37℃.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding CP-resistant OC cell lines A2780CP and SKOV3/CDDP were constructed by our laboratory. Sensitive parental A2780S cells and SKOV3 cells were co-cultured with 10–80 μM CP (Sigma-Aldrich, St. Louis, MO) for 48 h, during which the concentration of CP was gradually increased [ 23 , 24 ]. After resuscitation, these cells were cultured in DMEM (Gibco, Carlsbad, CA) containing 10% FBS (Gibco), 100 U/mL penicillin and 100 μg/mL streptomycin in a 5% CO 2 incubator (BB15, Thermo Fisher Scientific Inc., Waltham, MA) at 37℃.…”
Section: Methodsmentioning
confidence: 99%
“…NF-κB signaling pathway could be inhibited by miR-1301 to attenuate cisplatin resistance and delay the development of EMT in OC, ultimately refraining the progression of OC (Yu and Gao, 2020). Additionally, autophagy could be suppressed by miR-133a and miR-1301, thereby suppressing cisplatin resistance (Yu and Gao, 2020;Zhou et al, 2022). More importantly, the imbalance of ncRNA homeostasis was also closely related to the clinical characteristics of OC patients.…”
Section: Prognosis Values Of Autophagy-associated Ncrnas In Oc Patientsmentioning
confidence: 99%
“…found that miR-133a was significantly downregulated in CDDP-resistant OC cell lines A2780 and SKOV3. The overexpression of miR-133a significantly enhanced the CDDP sensitivity in CDDP-resistant A2780 and SKOV3 cells by inhibiting autophagy via directly targeting YES1 ( 45 ). Li et al.…”
Section: Mechanisms Of Ncrnas In Mediating Cancer Drug Resistancementioning
confidence: 99%